Pedagog wobec pluralizmu współczesnych teorii wychowania - Śliwerski, Bogusław (Horyzonty Wychowania, 2017)
The main problem undertaken by the author is presentinga pedagogue facing pluralism of contemporary theories of education.The author wonders what a teacher who is confrontedwith multitude of pedagogical theories should do, how to pullhimself together in the world of chaos and disorder, where pedagogicalapproaches and orientations are competing witch oneanother, not eliminating anything at the beginning. The authorrefers to the metaphor of „hypermarket and labyrinth”. Bothmetaphors illustrate the world of pedagogy resembling a similarmass of theories, ideas and philosophies. It is the supermarketsthat attempt to make the choice of diverse knowledge („goods”)available to society. Hypermarket becomes a peculiar kind oflabyrinth, a territory where customers should skilfully get around.Therefore, a question arises: How can pedagogue entangledinto the metaphor of hypermarket of theories of education avoidenslavement? The author thinks that he may simply not read, notstudy. He may adopt a critical attitude in the face of „catches”hidden in various theories. Finally, he may also look into his ownpedagogical consciousness thoroughly, analyze his own rationality,think about knowledge he needs. The author thus statesthat pedagogues are faced with the task of reading, classifyingand comparing a multitude of theories so that they can adoptthose most valuable and so that they are able to make use ofthem in the process of education.